0040 Effects Of Chronotype, Insomnia, Depression, And Age On Markers Of Systemic Inflammation In Nurses. (12th April 2019) - Walker, Jamie L; Slavish, Danica C; Messman, Brett; Wardle, Sophie; Dietch, Jessica R; Kohut, Marian L; Kelly, Kimberly; Ruggero, Camilo; Taylor, Daniel J
Abstract: Introduction: Insomnia, depression, and older age have been associated with elevated levels of systemic inflammation. Evening chronotype also is associated with impaired health, which may be partially mediated through increases in inflammation. However, it is not well understood how insomnia, chronotype, and depression may interact with age to predict inflammation. Nurses are an important population in which to study these associations, as rates of insomnia and depression are prevalent, which may be attributed to stressful work environments and rotating schedules. This study examined associations between insomnia, chronotype, age, and depression with inflammatory biomarkers in nurses. Methods: Participants were 400 nurses ages 18-65 (mean age = 39.03 ± 11.07; 91% female) recruited from two hospitals for a parent study ("Sleep and Vaccine Response in Nurses, " PIs: Taylor & Kelly). Participants completed surveys to assess demographics, mental health, insomnia symptoms, and chronotype. Approximately one month later, blood serum was obtained and analyzed for inflammatory biomarkers interleukin-6 (IL-6), C-reactive protein (CRP), interleukin-1 beta (IL-1β), and tumor necrosis factor alpha (TNF-α). Results: Controlling for age, gender, and race/ethnicity, chronotype was not associated with any of the inflammatory biomarkers. Greater insomnia symptoms were associated with higher IL-6 (b = 0.01, SE = 0.003, p = .003), and greater depressive symptoms were associated with marginally higher IL-6 (b = 0.01, SE = 0.005, p = .050). Older age was associated with higher levels of all inflammatory biomarkers (r = .10-.17, p &lt .05). There was an interaction between age and depressive symptoms, such that older individuals had a stronger positive relationship between depressive symptoms and IL-6 (b = 0.001, SE = 0.0005, p = .04). (Results are preliminary and will be confirmed with forthcoming additional data.) Conclusion: Our preliminary findings support previous research indicating positive associations between inflammation, age, and symptoms of insomnia and depression. Older nurses with greater depressive symptoms may be particularly at risk for elevated inflammation. Future longitudinal research should examine inflammation as a possible mediator between depression, insomnia, and other physical health outcomes. Support (If Any): NIAID R01AI128359-01